Broken Rings : Folksong and Occupational Transitions in the Maritime Provinces - Moreira, Jamie (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1991)
The retum of a disguised hero who tests the fidelity of his partner is one of the most commonly encountered thèmes in oral tradition. This paper seeks a localized interpretive frame for the motif by examining the “Broken Ring” ballads, with specific reference to their function in the fisher/lumbering communities of the Maritimes. It suggests that the two-dimensional imagery of the songs is a touchstone for a larger symbolic network, one which argues for sympathy where difficulties in human relationships are encountered due to occupational absences.